Revisiting institutional credibility of informal rental housing in Shenzhen: For dwelling function or exclusion function? - Ziqi Zhou; Yung Yau (Journal of Urban Management, 2023)
The credibility thesis premises that an institution's endogenous credibility and function, rather than its form, ensures its persistence. Informal rental housing (IRH), an informal housing institution in China, was suggested to serve as a dwelling for low-income residents in previous research on institutional credibility. Combining the institutional functionalism in credibility thesis and the relational and constructivist perspective in the strategic-relational approach (SRA), this research on two distinct SPRH cases in Shenzhen aims to re-examine the credibility thesis, moving the emphasis away from institutional functions toward the interaction between function and dysfunction, and their substitutability in the relation reconstruction dynamics. It reveals that the informal housing institution's credibility rationale has shifted in Shenzhen. Instead of serving a dwelling function, IRH is becoming an investment tool for profit-making and a part of public service for government targets, contributing to the credibility of informal housing and exacerbating the exclusion of the disadvantaged groups from urban areas. IRH's institutional credibility is contingent upon not just the endogenous institutional function, but also on the interplay of the function and dysfunction embedded in its institutional environment.